Integrated formal methods : 13th International Conference, IFM 2017, Turin, Italy, September 20-22, 2017, Proceedings /: 13th International Conference, IFM 2017, Turin, Italy, September 20-22, 2017, Proceedings. (2017) - Unknown
No abstract available